Composition Operators from the Weighted Bergman Space to the 𝑛th Weighted Spaces on the Unit Disc - Stevo Stević (Discrete Dynamics in Nature and Society)
The boundedness of the composition operator from the weighted Bergman space to the recently introduced by the author, the 𝑛th weighted space on the unit disc, is characterized. Moreover, the norm of the operator in terms of the inducing function and weights is estimated.